Solvometallurgical route for the recovery of Sm, Co, Cu and Fe from SmCo permanent magnets - Orefice, Martina; Audoor, Heleen; Li, Zheng; Binnemans, Koen (Separation and purification technology, 2019)
[Display omitted] •Solvoleaching is combined with non-aqueous solvent extraction.•Concentrated HCl had a similar leaching performance in water and ethylene glycol.•Extraction of cobalt was enhanced by addition of ethylene glycol.•Non-aqueous solvent extraction was carried out by Aliquat 336 and Cyanex 272.•Samarium was recovered as oxalate in high purity. A solvometallurgical recycling route for the recovery of samarium, cobalt, copper and iron from SmCo magnets was developed. The SmCo magnets were first crushed and milled to powder size and then leached in a 2 mol L−1 hydrochloric acid solution in ethylene glycol. Afterwards, cobalt, copper and iron were extracted from the leachate with 50 wt% Aliquat 336® in toluene, which was pre-saturated with 37 wt% HCl. The non-aqueous solvent extraction system improved the extraction efficiency of cobalt. The extraction was optimized by evaluating the extraction rates, the effects of temperature, feed/solvent ratio and the hydrochloric acid concentration. Through the construction of a McCabe-Thiele diagram it was possible to calculate the number of stages required for continuous extraction. Cobalt was recovered from the loaded solvent by stripping with a 0.5 mol L−1 aqueous hydrochloric acid solution. Copper was recovered by stripping with a 5 vol% aqueous ammonia solution, whereas iron precipitated under these conditions. The solvent could be reused after regeneration, i.e. evaporation of water and ammonia and reintegration of toluene and HCl. The samarium left in the raffinate was extracted by 20 vol% Cyanex 272 in n-dodecane. Finally, samarium was recovered from the loaded Cyanex 272 by precipitation stripping with a 0.2 mol L−1 aqueous oxalic acid solution. The purity of the recovered cobalt chloride was 98.3 wt% and that of samarium oxalate was 99.4 wt%.